(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, proposals and recommendations have been developed, identifying the internal opportunities for expanding the activities of non-governmental non-profit organizations operating in the Republic of Uzbekistan, identifying problematic aspects in the development of their activities and eliminating them. In addition, non-government non-profit organizations put forward practical suggestions on improving the regulatory and legal framework for the implementation of programmatic tasks and eliminating the shortcomings of the existing legislation. Furthermore, it is scientifically based that the strengthening of the legal basis of the activities of these organizations not only leads to their development, but also to the stabilization of the socio-economic potential of the country. In this, the rights of these organizations regarding the types of activities they can carry out today, the forms and specific features of their organization according to the procedures stipulated by the law, and the final conclusions are presented.